2001
DOI: 10.1118/1.1354627
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of human brain hemodynamics by simultaneous near‐infrared spectroscopy and functional magnetic resonance imaging

Abstract: The aim of this study was to compare functional cerebral hemodynamic signals obtained simultaneously by near infrared spectroscopy ͑NIRS͒ and by functional magnetic resonance imaging ͑fMRI͒. The contribution of superficial layers ͑skin and skull͒ to the NIRS signal was also assessed. Both methods were used to generate functional maps of the motor cortex area during a periodic sequence of stimulation by finger motion and rest. In all subjects we found a good collocation of the brain activity centers revealed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
245
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 350 publications
(256 citation statements)
references
References 10 publications
(15 reference statements)
9
245
1
1
Order By: Relevance
“…One possible explanation for these highly variable correlations obtained by Strangman et al (2002) were due to the near-infrared technique used in their study, which was a single source-detector method. Previously our group also used this technique (Toronov et al, 2001), and found that it is highly sensitive to superficial hemodynamic fluctuations in the scalp. These fluctuations bias the signals, thus reducing the correlation with the BOLD signal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One possible explanation for these highly variable correlations obtained by Strangman et al (2002) were due to the near-infrared technique used in their study, which was a single source-detector method. Previously our group also used this technique (Toronov et al, 2001), and found that it is highly sensitive to superficial hemodynamic fluctuations in the scalp. These fluctuations bias the signals, thus reducing the correlation with the BOLD signal.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years many NIRS studies have demonstrated that cerebral hemodynamic changes associated with functional brain activity can be assessed noninvasively in adult human subjects (Benaron and Stevenson, 1994;Obrig et al, 2000). Several types of brain activity have been studied, including motor activity Colier et al, 1999;Toronov et al, 2000Toronov et al, , 2001Franceschini et al, 2000), visual activation (Ruben et al, 1997;Kato et al, 1993), auditory stimulation (Sakatani et al, 1999), and the performance of different cognitive tasks (Chance et al, 1993;Villringer et al, 1993). Kleinschmidt et al (1996) were first to measure simultaneously the BOLD fMRI signal and hemoglobin changes using NIRS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Some devices offer interfaces to allow for multi-modal imaging and have successfully been used for example in simultaneous measurements of fNIRI and MEG (Seki et al, 2012), EEG (Hebden et al, 2012;Leamy and Ward, 2010), fMRI (Habermehl et al, 2012a;Toronov et al, 2001;X. Zhang et al, 2005) and other modalities.…”
Section: Overview Of Commercially Available Imaging Instrumentationmentioning
confidence: 99%